Urbanização de vilas e favelas e preservação de referências culturais: convergências possíveis? - Patrícia Fabiana Moura (2013)
This research aims to analyze the development of public policy of urbanization of villages and slums in Belo Horizonte and its interface with the preservation of cultural references in Aglomerado Santa Lucia. That cluster has its own history of occupation similar to the development of the capital, similar to other formations of villages and slums. It has been an important phenomenon that will structure the discussion in this study produced the channeling of resources from the Accelerated Grown Program (PAC) to the Vila Viva Program in Belo Horizonte - public policy of urbanization of villages and slums developed since 2005 and has between the main objects of intervention the implementation of infrastructure, production of decent housing, regularization of lands, rights of environmental sustainability, employment generation and community organization. In Aglomerado Santa Lucia the allocation of resources includes restructuring works on the road system, construction of public equipments, construction of Housing Units (UH), sanitation works and regularization of lands. In addition to the goals wanted by urban planning, the preservation of cultural references translated by memory, habits and local culture are permeated by urban intervention and an important focus of analysis in this study.